PENGARUH PUNISHMENT BEDA KERUDUNG DALAM MENINGKATKAN MAHĀRAH KALĀM SANTRIWATI IHYA ULUMUDDIN NUR SUFI’IYAH AMUNTAI - Akhmad Rusydi; Ahmad Khalidi; Zahratun Najirah (Sekolah Tinggi Agama Islam Al-Jami Banjarmasin, 2025)
The language program is a primary focus for enhancing the mahārah kalām (speaking skills) of female students (santriwati). Within this program, a color-coded headscarf system serves as an indicator of language violations. Each violation corresponds to a distinct type of headscarf punishment with varying colors. Although some types of headscarves have been discontinued, the punishment system remains active—particularly the “language security headscarf,” which has never ceased to be used. This indicates that linguistic discipline is a top priority for improving mahārah kalām at Pondok Pesantren Ihyā Ulumuddīn Nur Sufi’iyah. This study is a field research using a quantitative approach with a survey method. It aims to determine the effect of the colored headscarf punishment system on the improvement of mahārah kalām among santriwati. The population includes all high school-level female students, with a sample size of 38. Data collection techniques included observation, questionnaires, tests, and documentation. The data were analyzed using SPSS with tests for validity, reliability, normality, linearity, heteroscedasticity, and simple regression. The findings show that the colored headscarf punishment system influences the improvement of mahārah kalām, as evidenced by an r value of 0.406 and an R square value of 0.165. This suggests that 16.5% of the improvement is due to the punishment system, while 83.5% is influenced by other factors. The significance value of 0.011 (<0.05) confirms a statistically significant effect of the system on speaking skills at Ihyā Ulumuddīn Nur Sufi’iyah Amuntai